Influência do nidoparasitismo por chupim (Molothrus bonariensis) sobre a alimentação de filhotes em ninhos de sabiá-barranco (Turdus leucomelas) - Ferneda, Rafaela Vitti [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
About 1% of bird species are considered brood parasites. As an evolutionary response to losses caused by parasites, host species present antiparasitism strategies, which involve the detection and rejection of parasitic eggs and nestlings or the abandonment of the parasitized nest. However, little is known about the complex capacity of detection and rejection of offspring of parasitic species by hosts in Neotropical birds. The aim of this study was to identify a possible discrimination of the nestlings of the brood parasite shiny cowbird (Molothrus bonariensis) in feeding events by the thrush (Turdus leucomelas). More specifically, I tested the hypotheses that (1) the behavior of nestlings before being fed differs between the cowbird and the thrush species; (2) thrush nestlings are fed more often than cowbird nestlings; (3) the time it takes the adult to select the nestling to be fed is longer for the cowbird nestlings; and (4) the frequency with which thrush nestlings begs for food is higher in parasitized nests. Data were collected from video recordings made between 2015 and 2017 of nests found in the campus of the São Paulo State University “Júlio de Mesquita Filho” (UNESP), in Rio Claro-SP. Cowbirds were fed faster and more frequently than thrush nestlings, and induced an increase in the frequency of feeding visits by the parents, which was higher in parasitized nests. In addition, there were differences in the behavior of the two species before being fed: cowbirds begged more than thrush nestlings, in which the headraising behavior predominated. There was no difference in the behavior of the thrush in parasitized and non-parasitized nests. Results suggest that there is no clear distinction between the parasitic and their own nestlings by the parent thrushes.

Cerca de 1% das espécies de aves do mundo são consideradas parasitas de ninhos, uma vez que depositam seus ovos em ninhos de coespecíficos ou de outras espécies de aves, dependendo do cuidado parental dos hospedeiros para o sucesso de sua prole. Como resposta evolutiva às perdas causadas pelos parasitas, algumas espécies de hospedeiros apresentam estratégias antiparasitismo, que envolvem a detecção e rejeição dos ovos ou filhotes parasitas. No entanto, pouco se sabe sobre a complexa capacidade de detecção e rejeição dos filhotes de espécies parasitas por parte dos hospedeiros em aves neotropicais. O objetivo deste estudo foi identificar uma possível discriminação dos filhotes de chupim (Molothrus bonariensis), um nidoparasita, em eventos de alimentação dos filhotes pelo sabiá-barranco (Turdus leucomelas). Mais especificamente, testei as hipóteses: (1) o comportamento dos filhotes antes de serem alimentados difere entre as espécies; (2) os filhotes de sabiá-barranco são alimentados mais frequentemente que o filhote do parasita; (3) o tempo que o adulto leva para selecionar o filhote a ser alimentado é maior para o filhote parasita; (4) a frequência com que o filhote de sabiá-barranco pedincha por alimento é maior em ninhos parasitados. Os dados foram coletados a partir de um banco de gravações realizadas entre 2015 e 2017 de ninhos encontrados no campus Bela Vista da Universidade Estadual Paulista “Júlio de Mesquita Filho” (UNESP), em Rio Claro-SP. Os chupins foram alimentados mais rapidamente e frequentemente que os filhotes hospedeiros e induziram um aumento na frequência de visitas de alimentação, que foi maior em ninhos parasitados. Além disso, houve diferenças no comportamento das duas espécies antes de serem alimentados: os chupins pedincharam mais que os sabiás-barranco, nos quais predominou o comportamento de erguer a cabeça. Não houve diferença no comportamento dos sabiás em ninhos parasitados e não-parasitados. Os resultados desse estudo sugerem que não há uma distinção clara dos filhotes parasitas por parte dos pais de sabiá-barranco.
Influence of nest parasitism by shiny cowbird (Molothrus bonariensis) on the feeding of nestlings in pale-breasted thrush (Turdus leucomelas) nests
Keywords: Turdus leucomelas; Molothrus bonariensis; Nest parasitism; Parental behavior; Parental discrimination; Aves; Parasitismo; Comportamento parental; Discriminação parental; Parasitismo de ninho; Turdidae; Aves comportamento